What's China Got to Do With It? U.S. Alliances, Partnerships in the Asia‐Pacific. Issue 1 (16th January 2016) - Tow, William T.; Limaye, Satu
Abstract : U.S. alliances in the Asia‐Pacific are increasingly viewed as more than just threat‐centric policy instruments. Three core principles for alliance management underscore this reasoning: maintaining consensus about purpose and objectives; generating maximum alliance adaptability; and building capabilities to achieve full‐spectrum deterrence. The interests that compel U.S. regional allies to cooperate with Washington are this special issue's analytical focus. Evolving U.S. security partnerships in the Asia‐Pacific, the emergence of "hybrid" forms of security alignment, and Sino‐U.S. tensions complicate understanding the nature and politics of U.S. security alignments in the region. A Chinese "shadow" is likely to confront U.S. alliances and partnerships in ways which will compound strategic competition and tensions in the region. This reality impels the United States and its regional collaborators to understand and to coordinate each other's motivations for security cooperation as effectively as possible.